Mapping Research Trends on Metaverse-Based Multisensory Learning for Dyslexia: A Bibliometric Study - Handoko Handoko; Heni Jusuf (CV. Media Inti Teknologi, 2026)
Background: Research on immersive and multisensory learning for dyslexia has expanded alongside the development of augmented reality (AR), virtual reality (VR), extended reality (XR), and metaverse-based learning environments. These technologies offer promising opportunities to enhance learner engagement, accessibility, and literacy development. However, existing studies remain largely technology-oriented and conceptually fragmented, with limited efforts to synthesize multisensory, embodied, and affective learning principles into coherent pedagogical frameworks specifically designed for learners with dyslexia.Aims: This study maps research trends, thematic structures, and conceptual orientations in immersive and metaverse-based multisensory learning for dyslexia, and identifies research gaps that hinder the development of theory-driven instructional models.Methods: A descriptive bibliometric analysis was conducted on Scopus-indexed publications from 2020–2025. After screening, 54 studies were analyzed using keyword frequency and co-occurrence mapping, using VOSviewer to visualize to visualize conceptual relationships and thematic patterns.Results: The analysis reveals a gradual shift from technology-centered assistive tools toward increasing attention to learner engagement, inclusive design, the use of artificial intelligence, and pedagogical considerations. Nevertheless, key learning principles such as multisensory input, metaphor-based learning, embodied interaction, and affective support are mostly implemented as isolated design features rather than integrated instructional components.Conclusion: The findings suggest that metaverse-based learning systems are still predominantly conceptualized primarily as technological infrastructures rather than holistic learning ecosystems. This fragmentation indicates a significant need for integrated pedagogical frameworks that systematically combine multisensory, embodied, cognitive, and affective learning dimensions within immersive educational environments for learners with dyslexia.